Factorial CGE‐Based Analysis for the Indirect Benefits of the Three Gorges Project. Issue 4 (25th April 2023) - Han, Dengcheng; Huang, Guohe; Liu, Lirong; Zhai, Mengyu; Fu, Yupeng; Gao, Sichen; Li, Jianyong; Pan, Xiaojie
Abstract: Large‐scale hydraulic projects (LHPs) have become increasingly significant in river basin flood‐risk management. Although LHPs' direct flood‐retention benefits have been clearly shown, there has been a dearth of a comprehensive examination of their indirect implications, which can be more long‐lasting and substantial in both environmental and economic terms. Thus, this study develops a factorial computable general equilibrium (CGE)‐based LHP‐effect analysis approach (FLEA) to quantify the indirect impacts of LHPs and simulate postflood recovery strategies under diverse scenarios. The FLEA integrates a factorial analysis with a dynamic CGE framework, including a flood module that connects hydraulic initiatives to the economy during floods. The FLEA is applied to the Three Gorges Project (TGP). The results demonstrate that ∼$57 billion in Gross Domestic Product (GDP) and ∼12.9 Mt CO2eq reduction would be created annually through supply chains by the TGP. When floods strike, the TGP has the potential to save ∼$21 billion in GDP directly and reduce long‐term GDP losses by ∼50% throughout the reconstruction period. The TGP can have a considerable indirect impact on manufacturing. Furthermore, improved regulations and maintenance for the TGP may be desired for mitigating long‐term flood‐related losses, which is more crucial than aggressive postflood fiscal stimuli. Key Points: A factorial computable general equilibrium approach is developed to estimate the indirect impacts of large‐scale hydraulic projects The environmental and macroeconomic indirect impacts of the Three Gorges Project are investigated Increased maintenance and regulations of the Three Gorges Project can mitigate long‐term flood‐related losses